Immunohistochemistry in breast cancer. Tool needed today - Javier Martínez Navarro; Caridad Socorro Castro (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Molecular studies development in breast cancer has provided arguments to establish subclassifications of diagnostic and therapeutic importance, which are bringing to the daily practice the desirability of a patients personalized therapy, to better identify the type of neoplasia. Most current studies seek to phenotypically relate these subtypes to the classic factors reported in the breast cancer anatomopathological report, using conventional hematoxylin and eosin techniques. Immunohistochemistry is a reliable tool that allows subclassification of these neoplasms in different categories using markers, which can establish necessary parameters in diagnosis and prognosis. In this paper the main immunohistochemical markers used in Cienfuegos are presented as well as their usefulness.